Methyl Jasmonate: Putative Mechanisms of Action on Cancer Cells Cycle, Metabolism, and Apoptosis - Italo Mario Cesari; Erika Carvalho; Mariana Figueiredo Rodrigues; Bruna dos Santos Mendonça; Nivea Dias Amôedo; Franklin David Rumjanek (International Journal of Cell Biology)
Methyl jasmonate (MJ), an oxylipid that induces defense-related mechanisms in plants, has been shown to be active against cancer cells both in vitro and in vivo, without affecting normal cells. Here we review most of the described MJ activities in an attempt to get an integrated view and better understanding of its multifaceted modes of action. MJ (1) arrests cell cycle, inhibiting cell growth and proliferation, (2) causes cell death through the intrinsic/extrinsic proapoptotic, p53-independent apoptotic, and nonapoptotic (necrosis) pathways, (3) detaches hexokinase from the voltage-dependent anion channel, dissociating glycolytic and mitochondrial functions, decreasing the mitochondrial membrane potential, favoring cytochrome c release and ATP depletion, activating pro-apoptotic, and inactivating antiapoptotic proteins, (4) induces reactive oxygen species mediated responses, (5) stimulates MAPK-stress signaling and redifferentiation in leukemia cells, (6) inhibits overexpressed proinflammatory enzymes in cancer cells such as aldo-keto reductase 1 and 5-lipoxygenase, and (7) inhibits cell migration and shows antiangiogenic and antimetastatic activities. Finally, MJ may act as a chemosensitizer to some chemotherapics helping to overcome drug resistant. The complete lack of toxicity to normal cells and the rapidity by which MJ causes damage to cancer cells turn MJ into a promising anticancer agent that can be used alone or in combination with other agents.